PREDIKSI POROSITAS DAN SEBARAN FLUIDA GAS PADA RESERVOIR KARBONAT DI LAPANGAN X - MAILINTON (NIM : 22309010), THOMAS
Field X is located in the Nanggroe Aceh Darussalam is one field that is being explored by PT Medco Indonesia Tbk. Log data, core data and seismic data indicates that the field X has the potential to produce a hydrocarbon gas that is economical to exploit. The purpose of this study was to determine elastic properties of rocks that can be used to predict porosity and studied the distribution of natural gas fluid on carbonate reservoir Field X. Things are learned about the characteristics of carbonate reservoirs in Field X, namely porosity and fluid distribution of natural gas fluid by using simultaneous inversion method. Simultaneous inversion is included in the seismic inversion that using pre-stack data with AVO inversion technique. Inversion method utilizes the relationship between P and S wave velocity and density. Inversion is performed simultaneously for acoustic impedance P, acoustic impedance S, and density by using a three-domain angle that is near angle, mid angle, and the far angle. In addition, beside producing an inverted impedance (P & S) and inverted density, simultaneous inversion results are also used to derive the elastic parameters such as the lamda-rho (incompressibility), mu-rho (rigidity), lamda per mu, and Vp/Vs ratio. Crossplot analysis results showed that the acoustic impedance P has a linear trend of the porosity, so that the inversion results of acoustic impedance P can be used to predict the value of porosity in carbonate reservoirs. As for seeing the pattern of fluid distribution of gas used by Vp / Vs ratio because it provides the most obvious separation between the gas zone and wet zone. Porosity values above 10% spread in top (the build up) of the carbonate body facing toward the marine. The pattern of distribution of natural gas fluid in the reservoir also follow the pattern of distribution of porosity, so that it can be concluded that simultaneous inversion results give a good inversion results. Lamda-mu-rho parameters are not able to be a good indicator of the presence of fluid in the reservoir carbonate.